Antibacterial activity of methanol extract Rhizophora mucronata leaves toward Salmonella typhi: leading the typhoid fever - Rinto Muhammad Nur; Resmila Dewi; Sutriani Kaliu (Universitas Ahmad Dahlan, 2022)
The community has utilized Mangrove extensively, particularly as a component of traditional medicine. Rhizophora mucronata is one species that possess antibacterial, antiviral, antifungal, and insecticidal properties. According to reports, R. mucronata has antibacterial properties against the Salmonella typhi bacteria that cause typhoid fever. This research aims to obtain a methanol extract of R. mucronata leaves and assess its antibacterial potential as natural new medicine, particularly for treating typhoid fever. The extraction method is maceration with a 70 percent methanol solvent. Well, diffusion is utilized to determine antibacterial activity. Alkaloid, flavonoid, saponin, steroid, tannin, and triterpenoid are the chemical compounds identified in the methanol extract of R. mucronata leaves (MERmL). Ten percent concentration of MERmL exhibited moderate antibacterial activity (7.970.25 mm), whereas 30 percent concentration (11.380.29 mm) and 50 percent concentration (16.070.40 mm) exhibited intense antibacterial activity. Based on these findings, R. mucronata leaf methanol extracts with higher concentrations have more potent antibacterial activity against S. typhi in typhoid fever treatments.